Interaksi Sosial Anak Tunarungu di Lingkungan Sekolah Penyelenggara Pendidikan Inklusi ( Studi Kasus di SMP Pembangunan Laboratorium UNP) - Putri, Diana; Sopandi, Asep Ahmad; Marlini, Marlini (Jurnal Penelitian Pendidikan Khusus, 2022)
This study aims to determine how the social interaction of deaf children in the inclusive education provider school environment. Deaf children in social interactions have characteristics that tend to show sensitive, selfish, irritable behavior, irritability, lack of confidence and this is closely related to learning objectives. This research is a case study research. The research subjects are deaf children. Collecting data using observation, interview, and documentation techniques. The results of this study indicate that deaf children have social interactions with reciprocal communication and respond and show a friendly attitude and understand what is conveyed by the interlocutor, the subject communicates using spoken language (lip motion). Support from schools, teachers, parents, peers is a factor supporting the development of social interaction in everyday life, the subject hangs out with his friends widely. the subject controls his emotions and socially such as not easily angry and annoyed, not selfish and confident, thus making the subject easy to adapt to his environment.